Comparing the functional analysis of I-gel with Baska mask in laparascopic surgeries: an observational study - Shanmugavelu, G.; Kanagarajan, T. (International Journal of Research in Medical Sciences, 2018)
Background: More than 40% of general anaesthetics are managed with supraglottic airway devices. First generation SADs act as airway conduits whereas second generation devices have safety designs like integrated bite block, gastric drainage channel and act as airway conduit for endotracheal intubation. Supraglottic airway devices are getting accepted by many anaesthetists during laparascopic surgeries. Methods: Authors did a study, comparing the functional analysis of I- gel with Baska mask during laparascopic surgeries with controlled ventilation. The study was conducted on sixty patients of either sex scheduled for short duration laparascopic surgeries (<2 hs). The study conducted on ASA I and II patients with a BMI of <30kg/m2. Patients with restricted mouth opening(<2.5cm), difficult airway, known GERD patients, obese patients (>30kg/m2), and ASA physical status III and IV patients were excluded from the study. patients were induced with fentanyl 2µg/ kg, propofol 2-2.5mg/kg and neuromuscular paralysis facilitated with atracurium 0.5mg/kg. Anaesthesia was maintained with oxygen, air (fio2 40%) with isoflurane1.5-2%. Ease of insertion was evaluated using 4-points scale. Score 1 means easy insertion to score 4 denotes impossible to insert. Oropharyngeal seal pressure was measured after five minutes of placement. FGF 5L/min was used after closing the APL valve at 70cm h2o, recording the pressure at which pressue is plateaued. Presence of sore throat, dysphagia and dysphonia were examined 2hrs and 24hrs post operatively. Results: The insertion time was shorter for I-gel (12.3±3.8secs) than Baska mask (20.1±8.1secs). Oropharyngeal leak pressure was significantly higher for Baska mask (24-32cmh20). Oropharyngeal airway morbidity was not significantly different between two groups. So, it has been decided that both airways are suitable for laparascopic surgeries, but I-gel was quicker to insert, but Baska mask gave good airway seal. Conclusions: In this study, authors have noticed that Baska mask will give good airway seal when compared with I-gel. But I-gel was quicker to insert than Baskamask. The main problem of the study was that it was not blinded.